Proprioception in musculoskeletal rehabilitation. Part 2: Clinical assessment and intervention. Issue 3 (June 2015) - Clark, Nicholas C.; Röijezon, Ulrik; Treleaven, Julia
Abstract Introduction Proprioception can be impaired in gradual-onset musculoskeletal pain disorders and following trauma. Understanding of the role of proprioception in sensorimotor dysfunction and methods for assessment and interventions is of vital importance in musculoskeletal rehabilitation. In Part 1 of this two-part Masterclass we presented a theory-based overview of the role of proprioception in sensorimotor control, causes and findings of altered proprioception in musculoskeletal conditions, and general principles of assessment and interventions. Purpose The aim of this second part is to present specific methods for clinical assessment and interventions to improve proprioception in the spine and extremities. Implications Clinical assessment of proprioception can be performed using goniometers, inclinometers, laser-pointers, and pressure sensors. Manual therapy, taping, and bracing can immediately enhance proprioception and should be used to prepare for exercise interventions. Various types of exercise (active joint repositioning, force sense, co-ordination, muscle performance, balance/unstable surface, plyometric, and vibration training) should be employed for long-term enhancement of proprioception.